Optimizing Cardioplegic Solutions: A Focus on Pharmaco-Cold Strategies: Optimasi Solusi Kardioplegia: Fokus pada Strategi Pharmaco-Cold - Zokirovich, Shamratov Shokir; Sabirovich, Yusupov Anvar; Arifovich, Saidov Maksud (Indonesian Journal of Innovation Studies, 2024)
This study investigates the impact of crystalloid cardioplegic solutions (CCS) on electrophysiological mechanisms and the contractile system during the diastolic phase. Extracellular solutions, categorized by ion concentration, demonstrate efficacy in inducing cardiac arrest through moderately elevated potassium or potassium-magnesium combinations, aligning with normal or slightly reduced sodium and calcium levels. Notably, the ease of equilibration with myocardial tissue enhances the protective effect, correlating with infusion volume and duration of action. However, drawbacks such as low buffering capacity and the need for reinfusion after 15-20 minutes are identified. This research sheds light on the dynamic relationship between solution composition, duration of action, and protective efficacy, providing valuable insights for refining cardioplegic protocols in cardiac surgeries. Highlights: Intracellular vs. Extracellular Impact: Explore ion concentration's influence on crystalloid cardioplegic solutions, emphasizing the choice between intracellular and extracellular formulations. Equilibration Dynamics: Investigate the direct correlation between infusion volume, duration of action, and the protective effect, emphasizing equilibration with myocardial tissue. Refining Cardioplegic Protocols: Identify limitations like low buffering capacity, necessitating reinfusion, and offer insights into strategies for enhancing cardioplegic protocols in cardiac surgeries. Keywords: Cardioplegia, Intracellular Solutions, Calcium paradox, Protective Efficacy, Cellular Metabolism